INVESTIGATION OF ELECTROLESS Ni-P-TiO2 COMPOSITE COATING ON AA7075 FOR SURGICAL TOOLS APPLICATION - SHOZIB, IMTIAZ AHMED (2021)
The absorption and dissemination of bacteria on the surface of medical equipment raises the risk of human infections